Detection of Rare Beta Globin Gene Mutation [+22 5UTR(G>A)] in an Infant, Despite Prenatal Screening. (14th April 2013) - Mahdavi, Mohammad Reza; Karami, Hosein; Akbari, Mohammad Taghi; Jalali, Hosein; Roshan, Payam
Abstract : Background . Beta thalassemia is one of the most common hereditary disorders worldwide. In Iran, it is frequently reported from northern and southern provinces. In order to prevent child birth to be affected by this complication, prenatal screening and diagnosis are carried out nationwide. However, in some instances, this program is unable to identify rare mutations leading to thalassemia. Case Presentation . A married couple, who took part in prenatal screening and diagnosis, gave birth to a child who is affected by thalassemia major. After several molecular examinations, a rare mutation [+22 5UTR (G>A)] in compound heterozygote state along with a common mutation [codon 8 (-AA)] was found. Conclusion . This case study suggests that more advanced molecular evaluations must be integrated in prenatal screening programs to identify rare mutations and antenatal diagnosis of thalassemia cases.